Oxidative stress and endoplasmic reticulum stress contributed to hepatotoxicity of decabromodiphenyl ethane (DBDPE) in L-02 cells. (January 2022) - Jing, Li; Sun, Yanmin; Wang, Ji; Zhou, Xianqing; Shi, Zhixiong
Abstract: Decabromodiphenyl ethane (DBDPE) is one of the most commonly used novel brominated flame retardants (NBFRs), and its mass production and widespread application have caused health threats to the human being. Existing studies have shown that DBDPE has hepatotoxicity. And we have found that DBDPE could change cytochrome P450 3A (CYP3A) expression levels in rat livers, whereas the mechanism is unclear. In this study, we exposed human normal hepatocyte (L-02) to DBDPE to further study the effect and mechanism of DBDPE on hepatocellular injury and liver metabolic enzyme CYP3A changes in vitro. The results showed that DBDPE caused L-02 cell viability decrease, lactate dehydrogenase (LDH) and transaminase release, ultrastructural damage, and apoptosis. Moreover, DBDPE exposure induced oxidative stress (i.e., increased ROS generation and MDA levels and decreased GSH content, SOD activity, and mitochondrial membrane potential) and endoplasmic reticulum (ER) stress in L-02 cells as evidenced by the elevated PERK and IRE-1α expression levels. These results confirmed that DBDPE is toxic to hepatocytes. Besides, the CYP3A expression level was decreased in DBDPE exposed L-02 cells. However, pretreatment of L-02 cells with antioxidant N-Acetyl-l -cysteine (NAC) and endoplasmic reticulum stress inhibitor 4-PBA inhibited DBDPE-induced oxidative stress, endoplasmic reticulum stress, CYP3A expression decrease, and apoptosis. Therefore, we demonstrated that DBDPE could exert toxic effects and decrease CYP3A expression on L-02 cells by inducing ER stress and oxidative stress. Highlights: DBDPE has significant cytotoxicity in L-02 cells. DBDPE could cause oxidative stress and endoplasmic reticulum stress in L-02 cells. DBDPE decreased CYP3A protein expression by inducing oxidative stress and ER stress.